Impact of a Healthy Retail Intervention on Fruits and Vegetables and Total Sales in Tribally Owned Convenience Stores: Findings From the THRIVE Study. Issue 6 (November 2021) - Williams, Mary B.; Wang, Wenyu; Taniguchi, Tori; Salvatore, Alicia L.; Groover, William K.; Wetherill, Mariana; Love, Charlotte; Cannady, Tamela; Grammar, Mandy; Standridge, Joy; Fox, Jill; Jernigan, Valarie Blue Bird
Background: Healthy retail interventions are a recommended intervention strategy to address diet-related diseases, such as obesity and diabetes; however, retail managers are concerned about their bottom line. This study's aim was to assess the impact of a healthy retail intervention on fruits and vegetables (FV) sales, as well as total sales, in tribally owned convenience stores where grocery stores are scarce. Method: We analyzed weekly sales data over the first 6 months of a healthy retail intervention. We assessed the proportion of sales from two FV baskets. The FV basket included all fresh, canned, and dried FV sold at stores; while the fruits, vegetables, and salads (FVS) basket included all FV items as well as all salads sold. We compared mean weekly sales rates in intervention and control stores over the 6-month period using generalized estimating equations models to account for repeated measures. Results: Mean weekly FV basket sales rates were higher in intervention stores than control stores in both Nations. Mean weekly FVS baskets sales were significantly higher in intervention stores than control stores in one Nation and were higher, but not statistically significant, in intervention stores in the other Nation. Total sales remained steady throughout the intervention period. Conclusions: The THRIVE (Tribal Health and Resilience in Vulnerable Environments) intervention increased FV sales without negatively affecting total sales. Policy and Practice Implications . Healthy retail interventions in tribal convenience stores, where many Native Americans living in rural areas shop due to scarcity of grocery stores, could improve diet-related disparities without reducing total sales.